Efektifitas akupresur terhadap tekanan darah pada ibu hamil dengan hipertensi dalam kehamilan (HDK) di wilayah kabupaten karawang - Silawati, Vivi; Azzahroh, Putri; Makhrus, Imam; Pertiwi, Rahayu (Universitas Jenderal Achmad Yani Yogyakarta, 2025)
Background: Hypertension is a health issue that, if not managed properly, can lead to serious complications, including death. Hypertension can be treated both pharmacologically and non- pharmacologically. One non-pharmacological therapy is acupressure.Objective: to determine the effectiveness of acupressure on blood pressure in pregnant women with Hypertensive Disorders in Pregnancy (HDP) in Karawang Regency. Methods: This quasi-experimental study used a pre- and post-test with control group design. The sample consisted of 30 pregnant women with HDP, divided into intervention and control groups. Results: The average systolic and diastolic blood pressures before and after acupressure therapy were 150.4 and 97.07 mmHg, decreasing to 144.13 and 91.73 mmHg, respectively. Statistical analysis using the t-test showed p-values of 0.002 for systolic and 0.02 for diastolic pressure, indicating that acupressure had a significant effect on blood pressure changes in pregnant women.Conclusion: Acupressure therapy is highly beneficial as an alternative treatment for managing hypertension in pregnant women. Health workers are encouraged to provide education on the use of acupressure therapy in addressing hypertension.